Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/1753425920928449
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microRNA-128-3p alleviates liver ischaemia–reperfusion injury in mice through repressing the Rnd3/NF‐κB axis

Abstract: Although liver ischaemia–reperfusion (I/R) injury remains the primary underlying reason for liver transplant failure or post-transplantation liver dysfunction, the underlying mechanism is still largely elusive. MicroRNAs (miRNA) are involved in multiple physiological and pathological processes, including inflammation. Here, we identified that the miR-128-3p/Rho family GTPase 3 (Rnd3)/NF‐κB axis might play a critical role in liver I/R injury. Our results demonstrated that the level of miR-128-3p was negatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Of note, the activation of p65 is essential for the development of DOX-mediated cardiotoxicity, and inhibition of p65 could attenuate DOX-induced cardiotoxicity [ 25 , 26 ]. A previous study found that repression of miR-128-3p could alleviate liver injury through the regulation of p65 [ 27 ]. Here, we also found that repression of miR-128-3p reduced p65 activity and expression, and decreased myocardial inflammation levels in DOX-treated hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the activation of p65 is essential for the development of DOX-mediated cardiotoxicity, and inhibition of p65 could attenuate DOX-induced cardiotoxicity [ 25 , 26 ]. A previous study found that repression of miR-128-3p could alleviate liver injury through the regulation of p65 [ 27 ]. Here, we also found that repression of miR-128-3p reduced p65 activity and expression, and decreased myocardial inflammation levels in DOX-treated hearts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Shen et al found that miR-24-3p protected against hepatic I/R injury in mice through the repression of STING signaling pathway (Shen et al, 2020). Mou et al reported that miR-128-3p inhibition could alleviate liver I/R injury through suppressing Rnd3/NF-κB axis in mice (Mou et al, 2020). Zhang et al demonstrated that miR-449b-5p attenuated hepatic I/R injury by targeting HMGB1 (Zhang et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al established that miR-142-3p was downregulated in the liver tissues after I/R, while upregulated miR-142-3p ameliorated liver injury by targeting myristoylated alanine-rich C-kinase substrate (MARCKS) ( 7 ). Other miRNAs, such as miR-125b, miR-128-3b and miR-450b-5p ( 5 , 6 , 8 ), are reportedly involved in liver I/R. miR-140-5p has been investigated extensively in tumor research, including glioma, breast and lung cancer, and hepatocellular carcinoma ( 13 , 14 , 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs or miRs) are a class of highly conserved, endogenous, small non-coding RNAs that play important regulatory roles in a variety of biological processes and usually inhibit the expression of target genes by binding to the 3'-untranslated regions (3'-UTRs) of target mRNAs (4). In liver I/R injury, miRNAs, such as miR-125b, miR-128-3p, miR-142-3p, miR-450b-5p, and miR-27a, participate in the regulation of liver I/R injury through inflammatory responses, oxidative stress, apoptosis, autophagy, and energy metabolism (5)(6)(7)(8)(9). miR-140-5p, also known as miR-140, was first identified in zebrafish in 2005 (10).…”
Section: Introductionmentioning
confidence: 99%